Influence of underground water seepage flow on surrounding rock deformation of multi-arch tunnel - Li, Xi-bing; Zhang, Wei; Li, Di-yuan; Wang, Qi-sheng (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2008)
Based on a typical multi-arch tunnel in a freeway, the fast Lagrangian analysis of continua in 3 dimensions(FLAC 3D ) was used to calculate the surrounding rock deformation of the tunnel under which the effect of underground water seepage flow was taken into account or not. The distribution of displacement field around the multi-arch tunnel, which is influenced by the seepage field, was gained. The result indicates that the settlement values of the vault derived from coupling analysis are bigger when considering the seepage flow effect than that not considering. Through the contrast of arch subsidence quantities calculated by two kinds of computation situations, and the comparison between the calculated and measured value of tunnel vault settlement, it is found that the calculated value(5.7–6.0 mm) derived from considering the seepage effect is more close to the measured value(5.8–6.8 mm). Therefore, it is quite necessary to consider the seepage flow effect of the underground water in aquiferous stratum for multi-arch tunnel design.